POTENSI ANTIOKSIDAN EKSTRAK AKAR METANOLIK UNCARIA GAMBIR ROXB.: BUKTI DARI UJI PENANGKAPAN RADIKAL DPPH - Silvy Arundita; Rahmayati Rusnedy (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Farmasi Riau, 2026)
The root of Uncaria gambir Roxb. remains relatively underutilized despite its potential as a source of phenolic compounds with significant biological activities. This study aimed to evaluate the antioxidant activity of the methanolic root extract of U. gambir using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Dried roots were extracted by maceration with 70% methanol, yielding 10.64% extract. Antioxidant activity was assessed at five concentration levels (6.25, 3.125, 1.562, 0.781, and 0.39 µg/mL). The extract exhibited a concentration-dependent increase in DPPH radical scavenging activity, demonstrating a strong linear correlation between concentration and percentage inhibition. The IC₅₀ value of the extract was determined to be 12.55 ± 0.01 µg/mL. For comparison, gallic acid as a positive control showed a lower IC₅₀ value of 3.06 ± 0.05 µg/mL, indicating stronger antioxidant activity as expected for a pure phenolic compound. Levene’s test indicated homogeneity of variances (p > 0.05). An independent samples t-test showed a significant difference in IC₅₀ values between the extract and gallic acid groups (p < 0.05). Although the extract displayed lower potency than gallic acid, its activity can be classified as strong. These findings provide preliminary evidence supporting the potential of U. gambir roots as a natural antioxidant source and warrant further phytochemical investigations to identify the bioactive constituents responsible for the observed activity.